Spatial analysis of bovine cysticercosis in the state of Mato Grosso do Sul, Brazil — The needs of interventions in animal and human populations - Pereira, Marcella Nunes; Rossi, Gabriel Augusto Marques [UNESP]; Lopes, Welber Daniel Zanetti; Almeida, Henrique Meiroz de Souza [UNESP]; Mathias, Luis Antonio [UNESP]; Soares, Vando Edésio; Vidal, Ana Maria Centola (Elsevier, 2017)
The Taenia saginata-cysticercosis complex is an important zoonosis for public health and an important cause of economical losses for beef supply chain in developing and industrialized countries. Despite some risk factors for high-occurrence areas have already been described, further studies are required to better understand its global epidemiology. So, this study focused on establishing the prevalence, spatial distribution and environmental and human population aspects correlated with bovine cysticercosis prevalence in the state of Mato Grosso do Sul, Brazil. To this, we used data of 7,415,998 animals slaughtered from all 79 municipalities located in this state. Cysticercosis prevalence showed spatial distribution dependence (Moran Index = 0.375, p = 0.01) and some areas presented higher risk. Positive correlations of bovine cysticercosis prevalence with human population density (R = 0.5712, p = 3.85 e − 08) and rainfall index (R = 0.631, p = 0.03) were observed. A negative correlation (R = − 0.4637, p = 2.096 e − 05) with cattle population size was also established. These results highlight the importance of adopting sanitary measures to prevent environment contamination, besides other prophylactic measures like the treatment of human patients in order to reduce the Taenia saginata-cysticercosis complex occurrence.
Keywords: Epidemiology; Geographic Information System (GIS); Parasites; Taenia saginata